Successful allogeneic bone marrow transplantation after massive gastrointestinal bleeding in a patient with myelodysplastic syndrome associated with intestinal Behçet-like disease. (2021) - Ishii, Arata; Tsukamoto, Shokichi; Mishina, Tatsuzo; Izumi, Shintaro; Nagai, Yurie; Yamazaki, Miki; Hino, Yutaro; Kayamori, Kensuke; Oshima-Hasegawa, Nagisa; Muto, Tomoya; Mitsukawa, Shio; Takeda, Yusuke; et al.
Abstract: A 45-year-old woman was diagnosed with myelodysplastic syndrome (MDS) with trisomy 8 and Behçet-like disease (BLD) with multiple colorectal ulcers. Nonspecific inflammatory cells were infiltrated in the intestinal mucosa, whereas fluorescence in situ hybridization (FISH) analysis revealed only sporadic trisomy 8-positive cells. She presented massive lower gastrointestinal bleeding early after bone marrow transplantation but achieved long-term remission of both MDS and BLD. This is the first report of massive gastrointestinal bleeding after transplantation for MDS with BLD. Based on FISH analysis, dysregulation of systemic inflammation may be involved in BLD rather than direct invasion by trisomy 8-positive MDS clones.